Biaya atau Investasi? Analisis Akuntansi Sosial terhadap Kesejahteraan Karyawan - Fety Aptasari; Muhammad Helmi Falah; Baiq Krisnina Maharani Putri; Ely Windarti Hastuti; Khairul Mujahidi (SUSTAINABLE, 2026)
This study aims to analyze how employee well-being is interpreted and represented in social accounting practices, particularly in the debate over whether employee-related expenditures are positioned as costs or investments. This study uses a qualitative approach with a case study design at PT Unilever Indonesia for the 2022–2024 period. Data were obtained from annual reports and sustainability reports, then analyzed using thematic content analysis to identify patterns in narratives, measurement, and accounting recognition related to employee well-being. The results show that the company consistently allocates resources for fair remuneration, competency development, occupational health and safety, mental well-being, and diversity and inclusion. These practices are supported by measurable and transparent quantitative indicators. However, all employee-related expenditures remain recorded as operating expenses in the financial statements. This finding reveals a duality of representation: strategically, well-being is framed as an investment in human capital, but technically, accounting still treats it as a current-period expense. This research emphasizes the importance of developing a more humanistic social accounting approach to representing human value within organizations